RECURRENT TUBERCULOSIS NOTIFICATION AND TREATMENT RESULTS IN THE ARKHANGELSK REGION - O. M. Mironyuk (Tuberkulez i Bolezni Lëgkih, 2014)
The purpose of the investigation was to study trends in the prevalence of recurrent pulmonary tuberculosis and the efficiency of treatment in patients of this group from the civil sector of the Arkhangelsk Region in 2003 to 2009. There is evidence supporting that the epidemic situation has been recently improved, with the incidence of recurrent tuberculosis decreasing from 12.4 in 2003 to 7.8 per 100,000 population in 2009. There was a significant rise in the rates of multidrug-resistant tuberculosis among patients with its recurrences (29.2 and 32.5% in 2003 and 2009, respectively; p = 0.009542). Among the recurrent cases of the disease, the rate of bacteriological diagnosis verification increased from 16.3% in 2003 to 78.0% in 2009. Drug resistance in Mycobacterium tuberculosis among the recurrences remains high. Among the bacillary patients with recurrences, the proportion of those with multidrug-resistant tuberculosis was 55% in 2003 and 55.7% in 2009. There was one case of broad-spectrum drug resistance in the pathogen in 2005, 2007, and 2009. During the follow-up, the therapeutic efficiency decreased; this was due to the large number of cases who discontinued treatment for multidrug-resistant tuberculosis.